2 K Cryogenic system with the thermal switch for measuring electrical properties of insulation materials. (September 2021) - Jia, Peng; Xu, Dong; Zhao, Yuchen; Qi, Haoying; Nishimura, Arata; Liu, Huiming; Zhang, Hengcheng; Huang, Rongjin; Li, Laifeng
Highlights: A cryogenic system for measuring electrical properties of insulation materials has been established. The thermal switch in the cryostat shortens the time of precooling and saves a lot of helium gas. Two modes in the cryogenic system: 4.2 K mode and 1.65 K mode. The cryogenic system realizes the coupling of low temperature and high voltage. Abstract: A cryogenic system has been established to measure electrical properties of insulation materials. The cryostat in the system contains two operating modes: 4.2 K and 1.65 K. A G-M cryocooler is used as cold source in these two modes. In 4.2 K mode, samples were directly cooled by the copper plates connected to the second stage of the cryocooler. In the 1.65 K mode, the helium gas is liquefied. The superfluid 4 He (He-Ⅱ) of 1.65 K was obtained by throttling and depressurizing the liquid 4 He (He-Ⅰ). The thermal switch in the 1.65 K mode can reduce the precooling time by 11.6 h and saved 22.5 L of helium. The transforming of the two modes is controlled by four threaded rods which are connected to the first and the second stage flange. The electrical test unit is designed, including the breakdown strength test and the flashover characteristics test with the voltage from 0 to 100 kV, which realizes the coupling of low temperature and high voltage.